Experts Evaluation of Flex Billboard On Study Technology for Teaching and Learning - Onojah Amos Ochayi; Olumorin Charles Olubode; Soetan Aderonke Kofo; Adedokun-shittu Nafisat Afolake; Onojah Adenike Aderogba; Alimi Adebayo Emmanuel (Universitas Pendidikan Indonesia (UPI), 2022)
There is a need for a method that will shift the attention to the learners, while the lecturers play the role of facilitator of learning. One of the methods that can promote this learning style is Study Technology. Study technology is a student-centered learning technique that helps the learner to study successfully by providing solutions to all barriers encountered in the process of studying. This study investigated experts’ Evaluation of flex billboard on study technology for teaching and learning. The findings established that the flex billboard is efficient to create an awareness on study technology and it can be operated without the use of electric power supply. It was however recommended that curriculum planner should include in its curriculum, orientation programmer for the pupils on study technology as this will aid or enhance learning process.